The 2018 American Academy of Allergy, Asthma & Immunology Foundation Faculty Development awardees - Ballas, Zuhair K. (Journal of allergy and clinical immunology, 2018)
Within the broad category of T-cell dysfunction, T-cell exhaustion is a form of T-cell immunometabolic dysfunction.4 It is characterized by poor effector function in the context of persistent antigen and is well studied in patients with cancer and chronic viral infection.5 Dr Henrickson hypothesizes that T-cell exhaustion can be seen in some patients with PIDs as a result of increased signaling downstream of the T-cell receptor. To better understand these connections, Dr Henrickson will focus on a subset of monogenic PIDs with amplified baseline T-cell receptor signaling pathways, either through decreased inhibition (eg, LPS-responsive beige-like anchor [LBRA] deficiency3 or cytotoxic T lymphocyte–associated antigen 4 [CTLA-4] haploinsufficiency6) or amplified activation (eg, gain-of-function phosphoinositide 3-kinase [PI3K] mutations7). Interestingly, IL-10–producing B cells produce more IgG4 than non–IL-10–producing B cells, and patients with food allergy have lower frequencies of IL-10+ B cells compared with healthy control subjects. [...]the intersection of IgG4 and IL-10 in patients with allergic tolerance is likely at the level of B cells, especially Breg cells.